Answer:
x = -2/3
Explanation:
We'll employ our knowledge of indices and exponential resolution to solve the problem.
First, we'll make efforts to resolve this figures such that the bases will be of thesame figure.
Our priority will be on "27" and "81"
27= 3*3*3
27 = 3^3
81 = 3*3*3*3
81 = 3^4
Therefore, let's solve now!
27^(x + 2) = 81
3^3 (x + 2) = 3^4
We'll then use the exponent 3 to expand the bracket that is 3(x+2)
3 ^ (3x + 6) = 3^4
The bases in 3 will cancel out! The equation becomes:
3x + 6 = 4
3x = 4 - 6
3x = -2
x = -2/3
Math is fun